It’s a long way to Tipperary - Bizzarri, Mariano (Organisms. Journal of Biological Sciences, 2017)
A recently published article by a widely diffused Italian newspaper (Il Corriere della Sera), claims that the “rate of curability of cancer, in the next 10-15 years will be astonishingly increased”. That exploit could mainly be attributed (no doubt on that!) to the claims made by new generation molecular drugs designed to single out and then to ‘block’ one or more genes involved in cancer “causation”.